INOVASI DAN TRANSFORMASI DALAM MANAJEMEN PENDIDIKAN ISLAM - nisa ul ulum (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
The current era of globalization will of course require a renewal and an increase in the quality of the community so that it can be ascertained that there will be various kinds of changes that occur in society, both in social and cultural aspects or in education, which of course will always experience development. With this change, of course, it will also have an impact on the development of science and technology which will also develop rapidly. This transformation and innovation will certainly be needed to bring up new ideas or a change and renewal, especially in Islamic education management. Islamic education management is the result of guidance in terms of management, education and Islam, namely the process of social interaction which is carried out by people to be able to achieve goals that are in organizations that have been oriented in accordance with Islamic teachings. This orientation in the process of education management will of course be used as a step in the transformation process which includes planning, organizing, moving processes and supervision that will be passed through effective cooperation. This innovation tends to discuss ideas or methods which are considered as something new which will be shown to a group of people or society.